Pathophysiology of Chronic Obstructive Pulmonary Disease - Milic-Emili, Joseph; Pecchiari, Matteo; D'Angelo, Edgardo (Current Respiratory Medicine Reviews, 2008)
In normal animals, cyclic airway closure and reopening during prolonged mechanical ventilation at low lung volumes causes histological damage of small airways, characterized by epithelial sloughing and lesion and/or rupture of alveolar-bronchiolar attachments, with a concurrent increase in airway resistance that persists after restoration of physiological end-expiratory lung volume. Peripheral airway injury should be therefore expected to occur when the closing capacity exceeds the functional residual capacity and tidal airway closure is regularly present during spontaneous breathing. On these basis, it is proposed that in smokers the transition from peripheral airway disease to chronic obstructive pulmonary disease is characterized by three sequential stages: Stage I, during which the closing capacity eventually exceeds the functional residual capacity, i.e. airway closure and reopening occur cyclically with breathing; Stage II, during which tidal expiratory flow limitation is eventually exhibited; and Stage III, during which dynamic hyperinflation progressively increases leading to dyspnea and exercise limitation. In this perspective, it is tidal airway closure and, probably, tidal expiratory flow limitation that promote peripheral airway injury, accelerate the abnormalities of lung function, and may determine which smoker is destined to develop chronic obstructive pulmonary disease.
Keywords: closing volume